Matrons and maids : regulating Indian domestic service in Tucson, 1914-1934 - Haskins, Victoria K. (Victoria Katharine), 1967- (University of Arizona Press, 2012)
This book recounts the fascinating story of the placing of Native American girls into the homes of white families for domestic service during their summer vacations from boarding schools run by the federal Office of Indian Affairs. It complicates our picture of womens work and the complex involvement of white women as agents of colonization.